Fracture processes imaging in concrete using nonlinear ultrasound. (June 2021) - Lott, Martin; Remillieux, Marcel C.; Garnier, Vincent; Ulrich, T.J.; Le Bas, Pierre-Yves; Deraemaeker, Arnaud; Dumoulin, Cédric; Payan, Cédric
Abstract: This paper shows the complementarity of two nonlinear ultrasonic imaging methods to characterize closed macro cracks in concrete. A time reversal mirror is used to locally probe and image the nonlinearity of a cracked region. Two nonlinear parameters are extracted to map the cracked region. The image obtained using the first parameter relates the harmonic generation due to the contact and frictional behaviors at the crack lips, correlated with vibro-thermography imaging of the same crack. The image obtained using the second parameter is based on the conditioning of the material induced by distributed micro cracks arising from the fracture process zone. These results show a great potential for characterization of fracture processes in concrete, with the possibility to uncouple the effects of the crack itself from surrounding distributed micro damage. Highlights: Nonlinear ultrasound can image and distinguish fracture processes in concrete. Nonlinear responses from the fracture process zone and the crack lips are separated. The results are correlated with vibro-thermography images.